TENDENCY TO BRUXISM IN PHYSIOTHERAPY TEACHERS AND CONSEQUENCES IN THE QUALITY OF LIFE - Costa, Joelma Magalhães da; Santos, Aline de Carvalho; Braga, Renata Bezerra; Melo, Tairine Correa de; Carvalho, Raisa Seabra; Oliveira, Joanne Figueiredo De (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Bruxism is characterized by the parafunctional act of tightening or grinding the teeth, which may occur in a conscious or unconscious way, during sleep or in wakefulness. It has become a growing concern in recent years due to its negative impact on quality of life (QOL) and also because it is considered an important risk factor for temporomandibular disorders. Objective: This study aimed to evaluate the QOL related to bruxism in physiotherapy teachers from a private institution through a questionnaire and their perception for such parafunction. Method: A cross-sectional, quantitative and exploratory study. The self-perception of bruxism was assessed through three questions from the Fonseca Anamnestic Indexand the perspective of QLV through the Quality of Life Questionnaire (SF-36), with a sample of 38 teachers of both genders. Results: Based on the results found, the level of statistical significance was set at p<0,05 for all tests. Among the 38 interviewees, 47,4% (n = 18) of professionals were observed with bruxism, with a higher prevalence in the female gender. Regarding the comparisons of QOL in relation to bruxism, a statistically significant difference was found in relation to the dimension of Pain (p=0,014), in which the mean for the bruxism group was (59,8) and without bruxism (78,5). Conclusion: There is a relation of the bruxism with the quality of life of the interviewees, and this habit mainly interferes in the domain of pain. Another aspect that was shown to be significantly associated with bruxism was nervous tension, in which the tense and nervous professionals were associated with self-perception of bruxism.